Sugar-Sweetened Beverage Intake Trends in US Adolescents and Their Association with Insulin Resistance-Related Parameters - Andrew A. Bremer; Peggy Auinger; Robert S. Byrd (Journal of Nutrition and Metabolism)
The purpose of this study was to evaluate current sugar-sweetened beverage (SSB) consumption trends and their association with insulin resistance-related metabolic parameters and anthropometric measurements by performing a cross-sectional analysis of the NHANES data during the years 1988–1994 and 1999–2004. Main outcome measures included SSB consumption trends, a homeostasis model assessment of insulin resistance, blood pressure, waist circumference, body mass index, and fasting concentrations of total cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides. Although overall SSB consumption has increased, our data suggest that this increase was primarily due to an increase in the amount of SSBs consumed by males in the high-SSB intake group alone. Multivariate linear regression analyses also showed that increased SSB consumption was independently associated with many adverse health parameters. Factors other than SSB consumption must therefore be contributing to the increasing prevalence of obesity and metabolic syndrome in the majority of US children.